ANALYSIS OF THE EFFECT OF INDUSTRIAL AGGLOMERATION AND LABOR FORCE ON ECONOMIC GROWTH IN EAST NUSA TENGGARA PROVINCE FROM 2019-2023 - Febrianti, Luthfiah; Tiwu, Maria I. Hewe; Sili, Maria A. Radji (Jurnal Manajemen Bisnis Dan Organisasi, 2025)
This study aims to analyze the effect of industrialagglomeration and the labor force on economic growth inEast Nusa Tenggara Province from 2019 to 2023. Aquantitative approach was used, employing a panel dataregression method that combines five years of time series dataand cross-sectional data from 22 regencies/municipalities inEast Nusa Tenggara Province. The panel data model used isthe Random Effect Model (REM). The results of this studyindicate that, partially, industrial agglomeration does nothave a significant effect on economic growth, while the laborforce has a significant effect on economic growth.Simultaneously, industrial agglomeration and the labor forcehave a significant effect on economic growth in East NusaTenggara Province.